Rationale, design and objectives of ARegPKD, a European ARPKD registry study - Ebner, Kathrin; Doyon, Anke; Sander, Anja; Weber, Lutz T.; Schaefer, Franz (BMC nephrology, 2015)
Autosomal recessive polycystic kidney disease (ARPKD) is a rare but frequently severe disorder that is typically characterized by cystic kidneys and congenital hepatic fibrosis but displays pronounced phenotypic heterogeneity. ARPKD is among the most important causes for pediatric end stage renal disease and a leading reason for liver-, kidney- or combined liver kidney transplantation in childhood. The underlying pathophysiology, the mechanisms resulting in the observed clinical heterogeneity and the long-term clinical evolution of patients remain poorly understood. Current treatment approaches continue to be largely symptomatic and opinion-based even in most-advanced medical centers. While large clinical trials for the frequent and mostly adult onset autosomal dominant polycystic kidney diseases have recently been conducted, therapeutic initiatives for ARPKD are facing the challenge of small and clinically variable cohorts for which reliable end points are hard to establish.
Gesehen am 06.07.2020